2019
DOI: 10.1155/2019/9568307
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Second Mesiobuccal Canal in Maxillary Molars in a Saudi Arabian Population: A Micro-CT Study

Abstract: The aim of this study was to determine MB2 canal detectability in maxillary first and second molars obtained from a Saudi population using micro-CT. Maxillary first (n=35) and second (n=30) molars were scanned with micro-CT technology. The number of canals was recorded, and in case of having more than one canal, the level of extracanal detection was analyzed. The presence of extracanal was categorized based on the level they were first detected. Among the maxillary first molars, 28 (80%) and six (17%) teeth ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
2
27
1
1
Order By: Relevance
“…More than 70 until 97% of maxillary first molar showed the occurrence of the second mesiobuccal canal [2,6] and this condition is similar for all of the ethnic groups [1]. In vitro studies indicated that a second canal is present in up to 90% of maxillary first molars teeth [3], while in vivo studies reported a lower prevalence of the second mesiobuccal canal (77,2%-79,8%) [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 70 until 97% of maxillary first molar showed the occurrence of the second mesiobuccal canal [2,6] and this condition is similar for all of the ethnic groups [1]. In vitro studies indicated that a second canal is present in up to 90% of maxillary first molars teeth [3], while in vivo studies reported a lower prevalence of the second mesiobuccal canal (77,2%-79,8%) [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The second mesiobuccal canal could be immediately detected in 70% of the maxillary first molar, once the pulp chamber is exposed [2]. The rest of the second mesiobuccal were observed at deeper levels in the root and this requires careful probing in the pulp floor [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the recent advances in endodontics have contributed to safe, predictable, and efficient root canal treatment. Such developments include digital radiography, cone beam computed tomography (CBCT), microcomputed tomography (micro-CT), dental operating microscope (DOM), thermomechanically treated nickel-titanium files, and improved obturation devices [14][15][16][17]. The aim of this case report was to describe the diagnosis and management of rare root canal configuration of a mandibular second molar, showing one canal in a single conical root, using the contemporary advancements in endodontics.…”
Section: Introductionmentioning
confidence: 99%